Fruit and Vegetable Intake in Relation to Lower Urinary Tract Symptoms and Erectile Dysfunction Among Southern Chinese Elderly Men: A 4-Year Prospective Study of Mr OS Hong Kong. Issue 4 (January 2016) - Liu, Zhao-min; Wong, Carmen Ka Man; Chan, Dicken; Tse, Lap Ah; Yip, Benjamin; Wong, Samuel Yeung-shan
Abstract : Abstract: The role of fruit and vegetable (FV) intake in relation to prostate health remains inconclusive. This 4-year longitudinal study aims to explore the association of FV intake and the development of lower urinary tract symptoms (LUTS, a cluster of chronic urinary symptoms occurring in bladder, prostate and urethra), incidence of symptomatic benign prostatic hyperplasia (BPH) and erectile dysfunction (ED) in Chinese elderly men. Data were obtained from a 4 years longitudinal study (Mr OS Hong Kong, the largest prospective study on bone health in Chinese elderly). Two thousand Chinese men aged 65 years and older were recruited from the local community, of whom 1998 (99.9%) at baseline and 1564 (78.2%) at 4-year follow-up reported data on LUTS, which were evaluated by a validated International Prostate Symptoms Scale (IPSS). Erectile function was evaluated by the International Index of Erectile Dysfunction-5 (IIEF-5) questionnaires at 2- (n = 386) and 4-year (n = 475) follow-ups. Dietary intake was assessed using a validated food frequency questionnaire at baseline. Analysis was conducted using multivariate linear and logistic regression. For total FV and most of their subclasses, moderate consumption had the lowest mean changes of LUTS; we thus applied the moderate levels as the reference in the regression models. The high levels of total FV intake (>350 g/1000 kcal/day) were significantly associated with reduced IPSS by scores of -1.174 ± 0.459 (or -17.3% of basal IPSS, P  = 0.011) relative to the moderate groups (250–350 g/1000 kcal/day). FV consumption had no significant association with the score change of ED or the odds of sexual activities at 4-year (all P  > 0.05). High intake of dark and leafy vegetables (>50 g/1000 kcal/day) significantly reduced the risk of LUTS progression by 37.2% [odds ratio (OR) (95% confidence interval, 95% CI): 0.628 (0.466∼0.848), P  = 0.002] or risk of symptomatic BPH by 34.3% [OR (95% CI): 0.657 (0.442–0.976), P  = 0.038] after 4 years compared with the moderate group (25–50 g/1000 kcal/day). Adequate FV intakes, especially dark and leafy vegetables, were associated with improved LUTS among Chinese elderly men, but lack an association with ED and sexuality. Abstract : Supplemental Digital Content is available in the text